Research of Downlink HARQ Mechanism in LTE TDD System - Fatang Chen; Cui Wan; Xi Fan (Dianxin kexue)
Based on a detailed research on the mechanism of downlink data transmission in LTE system，an errorfree HARQ solution to realize the downlink data transmission process was provided.According to the relations of the feedback delay，associated decision of feedback judgment and retransmission priority were adopted to complete the correspondence between them.A research on RTT of synchronous and asynchronous HARQ and the influence of different UL-DL configurations on HARQ RTT were also studied.Then a method to minimize RTT was put forward to provide reference for eNode B to choice configurations when providing different communication services.